Bivariate analysis of barley scald resistance with relative maturity reveals a new major QTL on chromosome 3H - Zhang, Xuechen (Sci Rep, 2019)
The disease scald of barley is caused by the pathogen Rhynchosporium commune and can cause up to 30–40% yield loss in susceptible cultivars. In this study, the Australian barley cultivar ‘Yerong’ was demonstrated to have resistance that differed from Turk (Rrs1 (Rh3 type)) based on seedling tests with 11 R. commune isolates. A doubled haploid population with 177 lines derived from a cross between ‘Yerong’ and the susceptible Australian cultivar ‘Franklin’ was used to identify quantitative trait loci (QTL) for scald resistance. A QTL on chromosome 3H was identified with large effect, consistent with a major gene conferring scald resistance at the seedling stage. Under field conditions, a bivariate analysis was used to model scald percentage of infected leaf area and relative maturity, the residuals from the regression were used as our phenotype for QTL analysis. This analysis identified one major QTL on chromosome 3H, which mapped to the same position as the QTL at seedling stage. The identified QTL on 3H is proposed to be different from the Rrs1 on the basis of seedling resistance against different R. commune isolates and physical map position. This study increases the current understanding of scald resistance and identifies genetic material possessing QTLs useful for the marker-assisted selection of scald resistance in barley breeding programs.